Evaluation of collared anteaters (Tamandua tetradactyla) presented in a wildlife health reference center of Sao Paulo state, Brazil - Bernegossi, Agda Maria [UNESP]; Rahal, Sheila Canevese [UNESP]; Melchert, Alessandra [UNESP]; Teixeira, Carlos Roberto [UNESP]; Lima, Fabio Henrique [UNESP]; Medeiros, Raphael Duarte; Silva, Aline Alves da (Revista Biota Neotropica, 2018)
Deforestation and road construction have inflicted negative effects on wildlife populations. To contribute to the comprehension and preservation of wildlife species, this study aimed to evaluate collared anteater presented to a reference center located in Sao Paulo state, Brazil. Furthermore, the locations where the animals were most frequently found were determined. Data on collared anteaters (Tamandua tetradactyla) examined at the Center for Medicine and Research in Wild Animals (CEMPAS) were evaluated retrospectively for a period of 13 years. A total of 46 collared anteaters was examined, comprised of 14 males, 10 females, and 22 without identifying information. On average, adult males weigh 4.41 kg while adult females weigh 4.95 kg. The most common admission circumstance was vehicular strikes (36.96%), followed by dog bites (21.74%); 23.91% were considered clinically healthy. Animal outcomes were 36.96% (n=17) reintroduced, 34.78% (n=16) fatalities, 15.22% (n=7) transferred to other institutions, and 6.52% (n=3) escaped from the enclosure; and 6.52% (n=3) presented no medical record information. The collared anteaters were found mainly in the municipal areas of Botucatu (21.73%), Sao Manuel (17.39%), Lencois Paulista (6.52%), and Bauru (4.34%), with SP-300 being the main highway associated with the occurrences. In conclusion, the main cause of lesion in the collared anteaters evaluated in this study was vehicular strike that that led to death. However, including all collared anteaters at least half of them had a positive outcome.
Keywords: Wild animal; highway; clinical evolution; anteater